LncRNA BISPR promotes the progression of thyroid papillary carcinoma by regulating miR-21-5p. (1st June 2018) - Zhang, Hong; Cai, Yuechang; Zheng, Li; Zhang, Zhanlei; Lin, Xiaofeng; Jiang, Ningyi
Our study attempted to verify the effect of lncRNA BST2 interferon-stimulated positive regulator (BISPR) on cell viability, propagation and invasiveness of thyroid papillary carcinoma (TPC) and the interactive relationship between BISPR and miR-21-5p. Microarray analyzed the aberrant expression lncRNA BISPR in TPC. BISPR and miR-21-5p as well as B-cell lymphoma-2 (Bcl-2) expressions in TPC cells were determined by quantitative polymerase chain reaction (qRT-PCR) and Western blot. Cell counting kit-8 (CCK-8) assay, dual luciferase reporter assay, and transwell assay were conducted to manifest cell viability, propagation, and invasiveness of TPC cells. Flow cytometry was performed to determine the apoptosis and cell cycle of TPC cells. Mouse xenograft model was built to testify the effect of BISPR on tumor growth. BISPR in TPC tissues was over-expressed. BISPR knockdown restrained the propagation and invasiveness and enhanced the iodine uptake of TPC cells. The tumor-forming rate reduced after BISPR knockdown. In addition, miR-21-5p was lowly expressed in cancer tissues. BISPR promoted the development of TPC cells by inhibiting miR-21-5p expression. Bcl-2 was suppressed by miR-21-5p and sh-BISPR. BISPR, which was over-expressed in TPC, improved TPC cell viability, propagation, and invasiveness. MiR-21-5p was lowly expressed in TPC which inhibited Bcl-2 expression. BISPR stimulated propagation and invasiveness of TPC cells by depressing miR-21-5p.